HIV-Related Stigma, Sexual Identity, and Depressive Symptoms Among MSM Living With HIV in China: A Moderated Mediation Modeling Analysis. Issue 2 (March 2022) - Mi, Tianyue; Lan, Guanghua; Yang, Xueying; Li, Xiaoming; Qiao, Shan; Shen, Zhiyong; Zhou, Yuejiao
Depression is one of the biggest health issues among men who have sex with men (MSM) living with HIV, where sexual identity might play an intricate role. Yet, findings of the relationship between sexual identity and depression were mixed and few studies explored its underlying mechanisms. This study aimed to examine the association between sexual identity and depression, and the potential mediating role of HIV-related stigma and moderating role of age. A cross-sectional survey was conducted among 203 MSM living with HIV in Guangxi, China. Participants provided information on sexual identity, depression, HIV-related stigma, and background information. Descriptive statistics, bivariate analysis, and path analysis were applied to examine our hypotheses. Bivariate analysis demonstrated that participants who self-identified as gay reported a lower level of HIV-related stigma and depression. Path analysis revealed an insignificant direct effect of identifying as gay on depression. Yet, the indirect pathway was significant, with identifying as gay being associated with a lower level of HIV stigma and thus a lower level of depression. This indirect effect was moderated by age. The conditional indirect effect was significant in the younger group yet ceased in the older group. The study provided information to better understand the effect of sexual identity on mental health among stigmatized sexual and gender minorities by highlighting the mediating effect of HIV-related stigma and the protective effect of age. Interventions targeting mental health of MSM living with HIV might consider placing greater emphasis on addressing HIV-related stigma among younger MSM.